La influencia del contenido visual en el marketing digital para el turismo gastronómico: The influence of visual content in digital marketing for gastronomic tourism - Trujillo Bazan, Jeferson Manuel (2024)
In the vibrant district of Barranco, the fusion of digital marketing with gastronomic tourism highlights the relevance of visual content in attracting consumers. This qualitative analysis, based on interviews with restaurants that leverage the digital environment, examines how digital marketing strategies can promote both tourism and local economic development. The results emphasize the critical importance of visual content on digital platforms to increase tourist interest, highlighting authenticity and quality as essential elements to convey Barranco’s unique culinary experience. The need for digital marketing strategies that are flexible and adaptable to current trends and changing consumer preferences is discussed. The study concludes that Barranco has considerable potential for the growth of gastronomic tourism, subject to effective management and the implementation of innovative digital marketing strategies. Collaboration among different sectors, along with the promotion of sustainable and authentic practices, is identified as key to the sustained progress of the industry. The creation of a digital gastronomic guide, proactive use of social networks for promotion, encouragement of business collaboration, design of enriching multisensory experiences, and provision of specialized training in digital marketing for entrepreneurs in Barranco’s gastronomic sector are suggested.